Intervention and disarmament - Towle, Philip, 1945- author.
1 online resource.
Keywords: "In this book, some of Philip Towle's major contributions are brought together to shed light on the Cold War and its aftermath. Intervention and Disarmament: In a Culturally Diverse World is useful for postgraduates and scholars interested in international affairs and warfare in the modern world"--